The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/agronomy13051287
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Foliar Fertilization on the Physiological Parameters, Yield, and Quality Indices of the Soybean Crop

Abstract: Presented research was carried out in 2021 and 2022 on the Felix soybean variety at the Agricultural Research and Development Station Turda, located in the Transylvanian Plain, Romania. In this experiment, complex fertilizer NPK 20:20:0 was applied as a basic fertilizer in a dose of 200 kg ha−1 at the sowing stage, to which foliar fertilizer Agro Argentum Forte treatment was added in different doses and at different application stages. The main purpose of the study was to identify the suitable stages of foliar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(57 reference statements)
0
0
0
Order By: Relevance
“…In our study, we found that foliar fertilisation with single-component pre-preparations did not negatively affect the values of the analysed gas exchange and chlorophyll fluorescence parameters. Bărdas et al [63] showed that foliar fertilisation would increase physiological parameters in soybean plants. Kobraee [64] showed that the application of Ze, Fe, and Mn had a significant effect on the chlorophyll concentration in the leaves of soybeans.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that foliar fertilisation with single-component pre-preparations did not negatively affect the values of the analysed gas exchange and chlorophyll fluorescence parameters. Bărdas et al [63] showed that foliar fertilisation would increase physiological parameters in soybean plants. Kobraee [64] showed that the application of Ze, Fe, and Mn had a significant effect on the chlorophyll concentration in the leaves of soybeans.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal regime from April to September 2016-2022 is presented in Table 1. The data recorded at the Turda Meteorological Station [58] indicate an increase in monthly temperatures (Table 1), with visible warming of the weather for the entire vegetation period, starting from the emergence phase. The average monthly temperature of April has decreased in the last two years, as recorded by S , imon et al [59], and is the only exception reported with regard to the average monthly growing season temperatures; the other temperatures exceeded the 65-year multiannual average, with deviations reaching up to 3-3.9 • C in the summer months when the reproductive organs are formed, greatly affecting the productivity elements.…”
Section: Climate Conditions During the Experimental Periodmentioning
confidence: 99%
“…The impact of mineral and organic fertilization on crop yield and crop quality is also a subject receiving less attention. The novelty of these studies is systematically decreasing despite the consideration of specialty crops, new features, or more precise measurement methods [49][50][51][52][53][54][55][56].…”
mentioning
confidence: 99%